2013
DOI: 10.1097/bot.0b013e3182820eba
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Multiple System Injury Benefit From Early Fixation of Unstable Axial Fractures? The Effects of Timing of Surgery on Initial Hospital Course

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 57 publications
2
38
1
6
Order By: Relevance
“…Time of hospital admission until the initiation of the operative procedure for femoral shaft fixation was documented as #12 hours or .12 hours, in consideration of previous literature. 8 In certain instances, patients with multiple traumatic injuries underwent nonorthopaedic procedures before definitive fixation of the femoral shaft. Patients who required an exploratory laparotomy were documented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time of hospital admission until the initiation of the operative procedure for femoral shaft fixation was documented as #12 hours or .12 hours, in consideration of previous literature. 8 In certain instances, patients with multiple traumatic injuries underwent nonorthopaedic procedures before definitive fixation of the femoral shaft. Patients who required an exploratory laparotomy were documented.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent literature supports the practice of definitive stabilization of femoral shaft fractures within 24 hours. [2][3][4][5][6][7][8] However, in an era of damage control orthopaedics, other investigations have offered different recommendations suggesting that hypoperfusion before early fixation is associated with increased mortality, 9 increased complications 10 and worse pulmonary function. [11][12][13] Lactic acidosis represents a state of hypoperfusion and is a predictor of multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Table 1) Coluna/Columna. 2015;14(2):152-6 …”
Section: Resultsmentioning
confidence: 99%
“…8,27,28,33,36,37 Mortality was reported in 16 studies, and was not taken into account in only two studies. 8,39 In the majority of studies, it was reported by fracture stabilization group (early vs. late), with a maximum percentage of 7.6% among the early treatment groups and 17% for the late groups.…”
Section: Fracture Fixation Approach and Techniquementioning
confidence: 99%
“…Многие исследования свидетельствуют о том, что ранний, в первые 24 ч после получения политравмы, окончательный остеосинтез бедренной кости оказы-вает противошоковый эффект, позволяет в короткие сроки активизировать пострадавших и уменьшить частоту системных осложнений: синдрома жировой эмболии [11], ОРДС, пневмонии [15], сепсиса, ТЭЛА и ПОН [16,[30][31][32]. Кроме того, сокращаются продолжи-тельность искусственной вентиляции легких (ИВЛ), пребывания пациента в отделении интенсивной тера-пии и общий срок стационарного лечения, существен-но улучшаются анатомо-функциональные результаты лечения [32,33].…”
Section: ранний остеосинтез и феномен «второго удара»unclassified